Natural history of bicuspid aortic valves and ascending aortic aneurysms: Aortic center experience. Issue 8 (9th May 2022) - Bellaire, Christopher P.; Tharakan, Serena M.; Roy, Jordan; Puskas, John D.; Di Luozzo, Gabriele
Abstract: Background and Aim: The American Association of Thoracic Surgery published guidelines in 2018 encouraging regular surveillance rather than surgical intervention for ascending aortic aneurysms under 5.5 cm in both bicuspid aortic valve (BAV) and tricuspid aortic valve (TAV) patients. Since then, there have been limited studies reporting outcomes, especially by valve type. We aimed to analyze clinical outcomes including survival and aortic events in a cohort of BAV and TAV patients with ascending aortic aneurisms followed conservatively with routine computerized tomography (CT) surveillance per current guidelines. Methods: We followed 188 patients in our clinic between 2016 and 2019; 147 had two or more CT scans which allowed measurement of aortic growth. Echocardiogram data was evaluated for each patient. We identified similar cohorts of BAV ( n = 32) and TAV ( n = 64) patients matched by age, sex, hypertension, smoking history, family history of aortic disease, coronary artery disease, and hyperlipidemia. Univariate and multivariate analyses of the unmatched cohorts were performed. Results: The mean aneurysm size was 4.3 ± 0.58 cm with 95% confidence interval (3.14, 5.46). This did not differ between BAV and TAV patients, nor did aneurysm growth rates. Overall adverse event rate (dissection, rupture, and death) was low for the entire cohort (BAV group, 3% and TAV group, 3.5%). Survival at 10 years for the entire cohort was 90 ± 32%. Conclusions: Regardless of aortic valve type, there was a similar natural history and low adverse event rate. In the absence of risk factors, conservative management can be accomplished with minimal risk to the patient.